PENGARUH DISIPLIN KERJA DAN WORK LIFE BALANCE TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN KARYAWAN DEALER HONDA SJMS PESANGGARAN - Pinkky Octav Victoria; Nyoman Gede Krishnabudi; Sudarsih Sudarsih; Almas Farah Dinna Dewi; Mochammad Farid Afandi (Study Program of Management Faculty of Economics and Business University of Jember, 2023)
This study aims to determine and analyze the influence of discipline work and work life balance on employee performance through commitmentemployees of the Honda SJMS Pesanggaran Dealer. The place of research is on Jl.Suprobo No.53, Banyuwangi. The research time is during January – June 2022. The research design uses explanatory research and respondents used as many as 35 employees where the sampling technique using a saturated sample. The type of data is qualitative data which quantified. Primary data sources come from questionnaires and from companies and secondary data comes from journals, books, and previous research. The analysis method uses path analysis. The results of the study using SPSS 26 software show that work discipline variables affect employee commitment, work life balance affects employee commitment, work discipline has an effect on employee performance, work life balance affects performance employees and employee commitment affect employee performance. Keywords: Work Dicipline, Work Life Balance, Employee Commitment, Employee Performance.